2015
DOI: 10.1371/journal.pone.0135218
|View full text |Cite
|
Sign up to set email alerts
|

LXR-Mediated ABCA1 Expression and Function Are Modulated by High Glucose and PRMT2

Abstract: High cholesterol and diabetes are major risk factors for atherosclerosis. Regression of atherosclerosis is mediated in part by the Liver X Receptor (LXR) through the induction of genes involved in cholesterol transport and efflux. In the context of diabetes, regression of atherosclerosis is impaired. We proposed that changes in glucose levels modulate LXR-dependent gene expression. Using a mouse macrophage cell line (RAW 264.7) and primary bone marrow derived macrophages (BMDMs) cultured in normal or diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…This was consistent with findings by Hussein et al. who demonstrated that d ‐glucose (25 m m ) suppressed LXR‐dependent expression of ABCA1 . Patel et al.…”
Section: Discussionsupporting
confidence: 92%
“…This was consistent with findings by Hussein et al. who demonstrated that d ‐glucose (25 m m ) suppressed LXR‐dependent expression of ABCA1 . Patel et al.…”
Section: Discussionsupporting
confidence: 92%
“…Regression in diabetic mice is associated with defective reduction of plaque CD68+ cells, suggesting increased macrophage retention or increased entry of monocytes despite lipid lowering (13,15). In a recent study we found that chronic high glucose significantly compromised LXR-dependent gene activation relative to normoglycemia in cultured bone marrow derived macrophages (16). Because of increased phosphorylation of LXRα at S196 in progressing plaques (12), we hypothesized that LXR function is impaired in diabetic mice through the same modification and contributes to the impaired regression.…”
Section: Introductionmentioning
confidence: 84%
“…In mice, PRMTs are also involved in various metabolic processes associated with human disorders. PRMT2 null mice are resistant to dietary-induced obesity (Iwasaki et al, 2010), and PRMT2 is a glucose-sensitive protein (Hussein et al, 2015). PRMT3 was shown to regulate lipogenesis in MEFs, as a cofactor to the liver X receptor a (LXRa), and increased expression of PRMT3 correlates with non-alcoholic fatty liver disease (Kim et al, 2015a).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%